EFFECT OF PARTICLE SIZES AND CONTENT OF ORGANIC MATTER SEDIMENT ON EPIPELIC DIATOM ABUNDANCE IN BAYUR BAY WATERS OF WEST SUMATERA - Sitindoan, Benni Mario K.; Siregar, Sofyan Husein; Nurrachmi, Irvina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
The aim of this study is to determine the water quality, the particle size (mm) and the organic matter content sediment, the type and abundance of epipelic diatoms, and the effect of particle size and organic matter content of the sediment on the abundance of epipelic diatoms at Bayur Bay Waters. This study was conducted in June - July 2019. The survey method was applied in this study and sampling location determine by purposive sampling. The resullt of measurement of water quality parameter ranged salinity 29 ‰ - 34 ‰, pH 7-8, current speed of 0,10 m/s – 0,53 m/s, temperature 30,330C - 31,670C. The sediment types are grouped into four types, namely gravel, sandy gravel, gravelly sand, and sand. The average of particle size (Mz) ranged -1,37 Ø - 0,80 Ø. The organic matter on sediment ranged 2,46% -6,36%. Eleven species of epipelic diatoms was recorded namely Amphora sp, Cocconeis sp, Diploineis sp, Halamphora sp, Melosira sp, Navicula sp, Nitzschia sp, Pinnularia sp, Stephanodiscus sp, Isthmia sp and Synedra sp. The average value of abundance range 2.836 – 10.812 ind/cm2. Epipelik diatom abundance was not significantly different between the stations. The effect of sediment particle size on the abundance of epipelic diatoms by 34,37%. The effect of content of organic matter sediment on abundance of epipelic diatoms in Bayur Bay Waters by 51,78%.